What do we actually know about exosomal microRNAs in kidney diseases? - Li, Qianyu; Zhang, Zhiping; Yin, Min; Cui, Cancan; Zhang, Yucheng; Wang, Yali; Liu, Feng (Frontiers in Physiology, 2022)
There are many different types of kidney diseases with complex causes, all of which will irreversibly progress to end-stage renal diseases if left untreated. Thus, early diagnosis and targeted treatment of kidney diseases are important. Exosomes are extracellular vesicles released by a variety of cells, they are ideal carriers of DNA, RNA, proteins and other metabolites because of their bilayer membranes. Almost all renal cells can secrete exosomes, studies on exosomal microRNAs in the field of renal diseases develops rapidly though they started late. In this review, we summarized the changes of the expression levels of exosomal microRNAs in different kidney disease, revealing their ability to serve as diagnostic and prognostic markers. We also analyzed their roles in the development of different kidney diseases, which provide directions for researches on molecular mechanism and therapy strategy of kidney diseases.